Asymmetric and Non-atmospheric Consumption Externalities, and Efficient Consumption Taxation - Paul Eckerstorfer; Ronald Wendner (Johannes Kepler University of Linz, Department of Economics, 2013)
We analyze the effects of a generalized class of negative consumption externalities (asymmetric and non-atmospheric) on the structure of effcient commodity tax programs. Households are not only concerned about consumption reference levels - that is, they gain utility from keeping up with the Joneses - they also exhibit altruism. Two sets of efficient tax regimes are compared, based, on a welfarist- and a non-welfarist optimality criterion, respectively. Altruism turns out not to be at odds with the consumption externalities. Rather, altruism implicates a bound on efficient utility allocations. A non-welfarist government tolerates less inequality than a welfarist one. In the welfarist (non-welfarist) case, first-best personalized commodity tax rates respond highly sensitively (barely) to whether or not a consumption externality is asymmetric or non-atmospheric. If personalized commodity tax rates are not available (second-best case), the tax rate on a non- positional good is typically different from zero for corrective reasons. For plausible functional forms and parameter values, numerical simulations suggest that second- best tax rates are rather insensitive with respect to both the optimality criterion and the nature of the consumption externality.
Keywords: D62; H21; H23; 330; Consumption externality; keeping up with the Joneses; optimal (commodity) taxation; genuine altruism; non-welfarist government